Efek Jus Pisang Tongka Langit (Musa troglodytarum) Terhadap Ginjal Mencit (Mus musculus) Model Malaria - Efraim Samson; Melati Sopacua; La Eddy (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2019)
High incidence of malaria cases encourage various treatments efforts including exploration of various local knowledge, related to utilization of medicinal plants. The tongka langit banana (Musa troglodytarum) is a unique and endemic plant species from Moluccas, wich based on public testimonies were belived to have ability to cure fever, hepatitis, malaria, increasing male stamina and make better kidney function. The purpose of this research was to examine the effect of tongka langit banana juice on the mice kidney (Mus musculus) of the malaria model. Twenty male mice were used which consist of 5 donor mice and 15 test mice further devided into 5 treatment groups, such as, K (+) group, K (-) group, P1 dose group with tongka langit banana intake (0,55 g/mice/day); P2 (0,65 g/mice/day); dan P3 (0,75 g/mice/day), each group consisted of 3 mice. The results showed, that feeding mice with tongka langit banana juice is effective to decreased kidney damages of mice malaria model, such as, hydropic degeneration, necrosis, and atrophy. Of the three dose given, 0,75 g/mice/day is the most effective dose.